Influence of physical exercise on health improvement in older adult cancer patients: a systematic review - Rafael Corrêa; Cristina Vaz de Almeida; Vasco da Fonseca; Benjamin Miranda Tabak (Frontiers in Public Health)
IntroductionPhysical exercise has shown evidence in the recovery of cancer treatment. Therefore, interventions that influence these patients to adhere to physical exercise may prove beneficial. This study aimed to identify the influence of physical exercise on health improvement in older adult cancer patients.MethodsThe inclusion criteria are according to the PICOS strategy. We conducted this systematic review by searching the electronic databases PubMed, Web of Science, Scopus, and Cochrane on February 21, 2024. The systematic review was registered in PROSPERO (CRD42024508547). Each article included in the review was assessed for study quality using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. The data was presented in tables and described qualitatively in the text.ResultsThe systematic search in the databases identified 3,593 articles. We filtered these articles and obtained 15 studies focused on our research question. Exercise interventions show evidence that individual, group, and home exercise, as well as multimodal exercise programs, have positive outcomes for the physical and mental health and quality of life (QL) of older adult cancer patients. However, the studies had limitations regarding polypharmacy and health literacy measures.DiscussionPhysical exercise interventions showed positive results in the recovery of physical and mental health and the quality of life of older adult cancer patients. Future studies could explore physical activity interventions with polypharmacy and health literacy measurement tools to identify specific interventions that optimize the health and quality of life of older adult cancer patients.Systematic review registrationPROSPERO (CRD42024508547), https://www.crd.york.ac.uk/PROSPERO/view/CRD42024508547.